The Relationship Between Psychological Well-Being and the Quality of Life of Elderly People Suffering from Osteoarthritis at Tamalanrea Jaya Health Center - Ramma, Irayanti; Suarnianti; BN, Indah Restika (Ammar Dharma Foundation, 2025)
Background: As life expectancy rises, the elderly population worldwide continues to grow, including in Indonesia. One of the most prevalent health issues among the elderly is osteoarthritis (OA), which can significantly impair their quality of life.Objective: This study aims to explore the relationship between psychological well-being and the quality of life of elderly individuals suffering from osteoarthritis at Puskesmas Tamalanrea Jaya.Methods: A quantitative descriptive correlational study with a cross-sectional design was employed. The study sample consisted of 58 elderly individuals diagnosed with OA, selected through total sampling. Psychological well-being was measured using Ryff’s Psychological Well-Being Scale (RPWB), and quality of life was assessed using the WHOQOL-BREF. Data were analyzed using Pearson correlation tests.Results: The study revealed a significant relationship between psychological well-being and quality of life in elderly individuals with osteoarthritis (p<0.05).Conclusion: The findings suggest that improved psychological well-being is associated with a better quality of life for the elderly suffering from osteoarthritis. Thus, interventions supporting the mental health of the elderly should be integrated into OA management strategies.